SOCIAL (NEW) MEDIA AND THE DEEPENING OF DEMOCRACY IN NIGERIA (2011-2015) - Jaja, Jones (Acta Scientiae et Intellectus, 2024)
The complimentary role which the social media performs has increased the level of complexity of Nigerian politics. The increase in information flow, especially at the informal level, has bridged the wide informational gap which existed for a long time between the government and the governed. Nigeria’s political history is tainted with several military incursions into governance. This was characterized by the intense emasculation of all informational avenues, especially the press. The aim of this paper is to analyze the roles of the social media in our society. It also seeks to rationalize the need for social media in a democracy and the inherent challenges, as they relate to the Nigerian experience. The paper concludes by taking into cognizance, the weak regulatory framework that should drive access and content generation.